Legal Analysis of the Imporance of Halal Certification for Sheshallbake Products (Review of the Consumer Protection Law and Halal Certification Regulations) - Lukas Christopher Wijaya; Mochammad Erwin Radityo; Bambang Fitrianto (Journal Evidence Of Law, 2026)
Halal certification has a strategic position in the food industry, including SheShallBake products, as it serves as a mechanism to protect consumers from ingredients that do not comply with Islamic law. How are the regulations for halal certification registration for SheShallBake products, and what are the responsibilities of business actors and the legal consequences for food products that do not have halal certification. This study uses a normative juridical approach to analyze positive legal provisions, as well as an empirical juridical approach through interviews with business owners to understand practices in the field. The findings show that halal certification provides safety guarantees for consumers through a comprehensive verification process and serves as a means of legal protection against potential violations. This research encourages increased awareness among business actors regarding the importance of halal certification and the need for more transparent and accountable regulations. Thus, the implementation of halal certification on SheShallBake products is expected to increase consumer confidence while strengthening the halal food industry sector in Indonesia.